Strategi Pemasaran Media Digital dalam Meningkatkan Diseminasi Data di Badan Pusat Statistik - Oki Heryanto; Engkus Kuswarno; Purwanti Hadisiwi (Neolectura, 2022)
The marketing strategy applied by non-profit organizations or government agencies is not much different from the marketing strategy of private companies, because both have products or services that need to be marketed for the benefit of consumers. One of the government institutions that requires a marketing strategy is the Central Statistics Agency (BPS) to meet the needs of data users and increase the dissemination of BPS products. The development of ICT in line with internet users in Indonesia is a promotional opportunity. This study aims to find out how the BPS digital media marketing strategy is to increase the dissemination of statistical data products. The method uses descriptive qualitative with a case study approach. Data collection is carried out by means of literature studies and observations in Central BPS, Central Jakarta, especially in the Directorate of Statistical Dissemination in the period January - September 2021. The results of research on digital marketing strategies used by BPS in increasing the dissemination of statistical data products are (1) through integrated statistics service website, (2) publishing softcopy books, (3) using QR codes, (4) launching the Allstats application, (5) infographics, (6) launching the Virtual Statistical Corner. The sales of printed books have decreased because they have been replaced by the ease of getting data online.